Did rest breaks help with acute fatigue among nursing staff on 12‐h shifts during the COVID‐19 pandemic? A cross‐sectional study. (5th July 2021) - Sagherian, Knar; McNeely, Clea A.; Steege, Linsey M.
Abstract: Aim: This study aimed to explore whether 30‐min rest breaks were as effective at lowering acute fatigue among 12‐h shift hospital nursing staff who cared for patients with COVID‐19 as among those who did not. Design: The study was cross‐sectional in design. Methods: Data from the SAFE‐CARE study collected online between May and June 2020 were used. A subsample ( N  = 338) comprised of nursing staff who reported working 12‐h shifts, and providing direct patient care in hospitals was used in this study. Data on socio‐demographics, work and rest breaks, and subjective measures of fatigue, psychological distress, sleep and health were used. Hierarchical multiple linear regression followed by stratified analyses was conducted to explore the relationships between rest breaks and acute fatigue among nursing staff groups with and without COVID‐19 patient care. Results: The sample, on average, had high acute fatigue. Around 72% reported providing care to patients with COVID‐19, and 71% reported taking rest breaks 'sometimes', 'often' or 'always'. In the group that cared for patients with COVID‐19, there was no significant relationship between rest breaks and acute fatigue ( p  = .507). In the group that cared for patients hospitalized for other reasons, rest breaks were associated with lower acute fatigue ( p  = .010). Conclusion: Our findings showed both the importance and inadequacy of rest breaks in reducing acute fatigue. The process of within‐work recovery is complex, and routine rest breaks should be facilitated by nursing management on hospital units during and after the COVID‐19 pandemic. Impact: Rest breaks may present an effective strategy in lowering fatigue. Although rest breaks were not associated with less fatigue among staff caring for patients with COVID‐19, other co‐workers experienced some fatigue recovery. For frontline nursing staff, routine rest breaks are encouraged, and a systematic evaluation pertaining the sufficiency of rest breaks during high work demands in future research is needed.